2005
DOI: 10.1002/lsm.20191
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal and vascular damage analysis of in vivo human skin in response to 595 nm pulsed laser irradiation

Abstract: This study has demonstrated that CSC with a high Weber number spray can decrease nonspecific thermal damage to the epidermis in response to laser irradiation in vivo. We have also established a positive correlation between gross purpura and the level of vessel wall apoptosis. Lasers Surg. Med. (c) 2005 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…An in vivo study 33 with normal human skin revealed that when the Weber number of R-134a droplets was increased from 1100 to 5100, the threshold radiant exposure for nonspecific thermal injury to the epidermis did not increase, although the average scores of epidermal damage decreased, indicating the limitation of this means in terms of enhancing Q.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…An in vivo study 33 with normal human skin revealed that when the Weber number of R-134a droplets was increased from 1100 to 5100, the threshold radiant exposure for nonspecific thermal injury to the epidermis did not increase, although the average scores of epidermal damage decreased, indicating the limitation of this means in terms of enhancing Q.…”
Section: Discussionmentioning
confidence: 92%
“…This time delay is believed to be sufficient to ensure a relatively calm cryogen film to form on the sprayed surface, but sufficiently short to allow for the majority of heat removal to occur during the spurt duration. 33 Biopsy specimens were taken from the irradiated sites by 6-mm punches, fixed in 10% buffered formalin, processed for histological sectioning, and stained with hematoxylin and eosin ͑H&E͒. Thermal injury to the epidermis was evaluated by H&E histological observations.…”
Section: Ex Vivo Dark Human Skin Samplementioning
confidence: 99%
“…Pikkula and colleagues were able to show that, dependent on the pulse length, prior cooling with cryogen spray and the dose administered, delayed reactions were observed [21], with biopsies taken 1.5 h after therapy. Assessable damage ranged from elongated basal-layer cells to complete dermal ablation, dependent on the flow (8-30 J cm −2 , the single pulse length was 0.1 µs).…”
Section: Discussionmentioning
confidence: 99%
“…Collateral injury is evident on histological examination. Cellular damage is evidenced by basal cell elongation, cytoplasmic vacuolization, nuclei shrinkage, formation of multiple basal lacunae, subepidermal separation, and epidermal ablation [1]. Vascular changes may be seen in the form of intravascular thrombosis, endothelial cell detachment from the basement membrane, or even vessel destruction and erythrocyte extravasation.…”
Section: Introductionmentioning
confidence: 99%